Velhice: complexa idade - o paradigma da complexidade e sua importância para o campo da gerontologia - Neves, Suhaila Ahmad Harati das (2013)
As Gerontology is recognized as an interdisciplinary field of knowledge, due to its object (the human being aging process and old age), it is committed to a theoretical and methodological articulation of knowledges constituted in many disciplinary fields. Being a process as well as a human condition, I discussed the Complexity Paradigm principles in the first chapter. After all, stating the human being is complex is not exactly new. Facing the complexity at issue seems to be a challenge for those willing to do so. Reason enough (at least for me, in this dissertation) to bring to light a way of seeing / reading the human being, herein represented by Morin (1951, 1973, 1986, 1990, 1994, 1999, 2000). His propositions were discussed in light of the need (recognized by scientific fields) to attain some "relevant" knowledge about a fact or a phenomenon in particular. Discussing the Complexity Paradigm principles, I have come to a first conclusion on its relevance to the theorization developed in the field of Gerontology. In the second chapter, I focused on the theoretical and methodological distinctions between multi-, inter-and transdisciplinarity, aiming at identifying how relevant the articulation of each of these approaches with said Complexity Paradigm is. Besides Morin, other authors have been referred to (Clotet 2007; Etges 1995; Feriott 2007; Ferraro and Chan 1997; Mora 1998; Severino 1995, Silva 2007; Padua 2008; Teixeira, 2007). Further clarification has been given to me of transdisciplinarity as being what the philosopher considers the most appropriate approach guiding the Paradigm, that is, Complexus means what has been woven together (MORIN, 1999, p.38). In the third chapter, I bring up some theorization developed in Gerontology so as to forward a reflection on whether the Complexity Paradigm can (and how) contribute to the construction of a relevant knowledge of a process and a condition specifically when human beings are at issue. Besides, I try to identify if, in this field, transdisciplinarity is cited - and what the reasons to do so are - as it is the most theoretical and methodological approach in line with the Paradigm aforementioned. I conclude by pointing out that the Complexity Paradigm, in so far as its theoretical and methodological developments are concerned, may constitute a space of affiliation to build an original (transdisciplinary), consistent and relevant theorization in the Gerontology field. Original and consistent because it is methodologically attuned to the inherent complexity of the object being investigated and relevant because it provides room to guide actions / behaviors that meet the specific demands of the elderly population segment, the basis for the construction of a new professional profile